ANALISIS RISIKO OPERASIONAL MENGGUNAKAN METODE FMEA STUDI KASUS PEKERJAAN INSTALASI PERALATAN OPERASI TERMINAL - Linsy Shafa Kamila; Aditya Maharani; Fitri Hardiyanti (Proceeding Maritime Business Management Conference, 2024)
Port operations using conventional RTG (Rubber Tyred Gantry) results in an increased operational cost burden as maintenance costs and diesel fuel prices continue to increase every year. Therefore, a power source change was made by using electrical energy through container loading and unloading equipment installation work. However, the implementation of implementation of the work raises various possibilities and risk impacts that need to be anticipated. One of them is the risk that can hinder the smooth work and cause significant delays. This research aims to determine the potential risks of work that may occur. The analysis uses the Failure Mode and Effect Analysis (FMEA) method. The results show that there are 20 potential risks with 6 of them being prioritized risks.